Konsep The concept of BMT from the perspective of QS Al-Baqarah verse 188 - Anisa Gustriani; Gustiya Sunarti (Yayasan Darussalam Bengkulu, 2025)
This research aims to understand the concept of BMT (Baitul Maal wa Tamwil) from the perspective of Q.S. Al-Baqarah verse 188. This verse prohibits the acquisition of another's wealth unjustly or through unfair legal means. This research uses a qualitative approach with a hermeneutic method to interpret the verse's meaning and apply it to BMT practices.